2017
DOI: 10.1186/s12879-017-2627-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunological recovery in tuberculosis/HIV co-infected patients on antiretroviral therapy: implication for tuberculosis preventive therapy

Abstract: BackgroundUnderstanding the immune response to combination antiretroviral therapy (cART) is essential for a clear approach to tuberculosis (TB) preventive therapy. We investigated the immunological recovery in cART-treated HIV-infected patients developing TB compared to those who remained free of TB.MethodsWe extracted data of HIV-infected patients from a multicenter cohort for the HIV clinical surveillance in Germany. No patients included in our study had TB at the beginning of the observation. Using a longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
2
10
0
7
Order By: Relevance
“…Few studies have reported long-term trends in post-ART CD8 + cell counts. Two years post-ART, two studies reported similar findings to ours, of continued declines in CD8 + cell counts [ 18 , 21 ], whereas three studies reported stabilized CD8 + cell counts at elevated levels (approximately 600–900 cells/μl) [ 12 , 17 , 19 ]. However, sample sizes in these studies were small compared with ours (≤1253), and the patient population was heterogenous, consisting of late presenters or a mixture of treatment naïve and treatment experienced patients.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Few studies have reported long-term trends in post-ART CD8 + cell counts. Two years post-ART, two studies reported similar findings to ours, of continued declines in CD8 + cell counts [ 18 , 21 ], whereas three studies reported stabilized CD8 + cell counts at elevated levels (approximately 600–900 cells/μl) [ 12 , 17 , 19 ]. However, sample sizes in these studies were small compared with ours (≤1253), and the patient population was heterogenous, consisting of late presenters or a mixture of treatment naïve and treatment experienced patients.…”
Section: Discussionsupporting
confidence: 75%
“…The benefits of ART for recovery of CD4 + cell counts are well documented [ 14 16 ]. However, few studies have investigated long-term trends in CD8 + cell counts [ 17 21 ] and in CD4 + : CD8 + ratio [ 17 24 ] after starting ART, with almost all based on small (<150) or moderate (<2000) sample sizes. Given the potential health implications of elevated CD8 + cell counts and CD4 + : CD8 + ratios below 1 [ 19 , 20 , 25 ], more information is needed about their long-term trends in treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Median CD4/CD8 ratio at time of ART initiation in patients who developed incident TB in our cohort was similar to recent reports [18,44]. However, no significant difference in the average change of ratio over time on ART was seen in patients developing TB compared to patients remaining free of TB [44].…”
Section: Discussionsupporting
confidence: 90%
“…In light of this, cHIV/HBV was previously shown to result in slow CD4+ T-cell recovery in these patients compared to PLWHIV only [ 9 , 42 ]. TB also results in slow CD4+ T-cell recovery even after ART initiation [ 43 , 44 , 45 ]. In one South Africa cohort of 15,646 adults, there was no difference in immune restoration between participants with cHIV/TB and those without TB after ART initiation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%